2016
DOI: 10.5152/jtgga.2016.16129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of metformin and oral contraceptive combination of ethinyl estradiol and drospirenone in polycystic ovary syndrome

Abstract: Metformin is effective in regularizing menstrual cycles, decreasing body mass index, and treating hyperandrogenism in Indian women diagnosed with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Estrogen supplementation can effectively relieve symptoms such as oligomenorrhea and amenorrhea in adolescents with PCOS during the process of growth [25]. ER is critical for differentiation of GCs and ovulation, and a positive correlation was observed between the expression of ER and aromatase in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen supplementation can effectively relieve symptoms such as oligomenorrhea and amenorrhea in adolescents with PCOS during the process of growth [25]. ER is critical for differentiation of GCs and ovulation, and a positive correlation was observed between the expression of ER and aromatase in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…A six-month, open-label, randomized trial by Ganie et al 82, of low-dose spironolactone and metformin combination than either drug alone, showed the superiority of the former in terms of improved clinical parameters and compliance to treatment. A comparison of metformin and OCP (EE plus drospirenone) was done as a prospective observational study (n=46) over one year by Suvarna et al 83, and metformin alone was found to be equally effective in regularizing menstrual cycles and treating hyperandrogenism in Indian women with PCOS. Use of non-hormonal options i.e ., metformin and spironolactone, after a period of oral contraceptive use, was retrospectively studied by Kulshreshtha et al 84, in a small group of women with PCOS for regularization of their menstrual cycles.…”
Section: Management Of Pcosmentioning
confidence: 99%
“…De Leo et alin their study of the effect of oral contraceptives on markers of hyperandrogenism and levels of SHBG in PCOS patients found similar results, they concluded that oral contraceptives particularly those containing antiandrogenic progestogens as drospirenone proved more effective in counteracting the high androgen levels in those patients [9]. Suvarna et alin a study that aimed to compare metformin versus ethinylestradiol/drospirenone OCP in PCOS they noted that after 3 months of OCP use there were significant reduction in DHEAS and testosterone levels [10]. These results are in line with the earlier studies that investigated the use of drospirenone-containing OCP in the treatment of PCOS.…”
Section: Discussionmentioning
confidence: 91%